2022
DOI: 10.1038/s41467-022-32165-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-coupled and epigenome-encoded mechanisms direct H3K4 methylation

Abstract: Mono-, di-, and trimethylation of histone H3 lysine 4 (H3K4me1/2/3) are associated with transcription, yet it remains controversial whether H3K4me1/2/3 promote or result from transcription. Our previous characterizations of Arabidopsis H3K4 demethylases suggest roles for H3K4me1 in transcription. However, the control of H3K4me1 remains unexplored in Arabidopsis, in which no methyltransferase for H3K4me1 has been identified. Here, we identify three Arabidopsis methyltransferases that direct H3K4me1. Analyses of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 105 publications
4
34
1
Order By: Relevance
“…The current study indicated that five ATX proteins function redundantly and are required for plant viability, suggesting that the ATX proteins play a critical role in plant growth and development. Although the effect of atx mutations on H3K4me1 was not detected in the current study, the H3K4me1 level was significantly reduced in the atx1/2 mutant as reported by a recent study (Oya et al, 2022). Of note, the atx1 mutant allele (SAIL_409_A10) used in the current study is different from the atx1 allele (SALK_149002C) used in the previous study, which may cause different effects on H3K4me1.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The current study indicated that five ATX proteins function redundantly and are required for plant viability, suggesting that the ATX proteins play a critical role in plant growth and development. Although the effect of atx mutations on H3K4me1 was not detected in the current study, the H3K4me1 level was significantly reduced in the atx1/2 mutant as reported by a recent study (Oya et al, 2022). Of note, the atx1 mutant allele (SAIL_409_A10) used in the current study is different from the atx1 allele (SALK_149002C) used in the previous study, which may cause different effects on H3K4me1.…”
Section: Discussioncontrasting
confidence: 51%
“…In Arabidopsis, histone H3K4 methylation was found to be catalyzed by different histone methyltransferases, including ATX1-5 (Alvarez-Venegas et al, 2003;Saleh et al, 2008;Chen et al, 2017;Oya et al, 2022), SDG2/ATXR3 (Berr et al, 2010;Guo et al, 2010), and ATXR7 (Berr et al, 2009;Tamada et al, 2009;Oya et al, 2022). However, how different types of histone methyltransferases cooperate to regulate histone H3K4 methylation was largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ATX1, ATX2, ATXR7 are responsible for the enrichment of H3K4me1 in the gene bodies of active genes (Oya et al 2021). Tudor domain of PDS5C binds H3K4me1 and facilitates homology directed repair (HDR) (Niu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, H3K4me1 marks gene bodies of active genes. Recent work has demonstrated that H3K4me1 enrichment is mediated by a combination of transcription-coupled (ATXR7) and epigenome-guided (ATX1, ATX2) methyltransferases (Oya et al, 2021). Once established, H3K4me1 reading can occur by proteins containing histone-reader domains such as “Royal family” Tudor domains, which bind methylated lysine residues on H3 histone tails (Kim et al, 2006; Lu and Wang, 2013; Maurer-Stroh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ATX1, ATX2, ATX3, ATX4, ATX5, ATXR2, ATXR7, SDG2, and SDG4 catalyze preferentially the H3K4me3 mark, whereas H3K4me2 is catalyzed by ATX2, ATX3, ATX4, ATX5, and the H3K36me3 by ATXR2, SDG26, SDG8, and SDG4 [ 16 , 17 , 18 , 22 , 24 , 25 , 26 , 29 , 31 , 48 , 49 ]. A dual function has been reported for ATX1, ATX2, and ATXR7, which also seem to catalyze the H3K4me1 mark deposition [ 24 , 50 ]. The reported specificity of these HMTs ( Table 1 ) is based mainly on analyses of loss-of-function mutants but not on biochemical analyses, being analyses performed at a specific developmental stage, without considering their different interactions or other factors that could be necessary for specificity.…”
Section: What Does It Mean To Be a Trxg Member?mentioning
confidence: 99%